Interplay between COVID-19 and Secukinumab treatment in Spondylarthritis patients during the omicron surge: a retrospective cohort study - Tong Wu; Yanhong Li; Deying Huang; Yinlan Wu; Xiuping Liang; Lu Cheng; Zehui Liao; Fang Xu; Ye Chen; Jing Zhao; Zijing Xia; Chunyu Tan; et al. (Taylor & Francis Group, 2024)
AbstractThe objective of this retrospective cohort study was to assess the relationship between Corona Disease 2019 (COVID-19) and Secukinumab treatment in patients with Spondylarthritis (SpA) in China during the omicron surge. Researchers retrieved 1018 medical records of Secukinumab-treated patients between January 2020 and January 2023 from the West China Hospital of Sichuan University. Out of these, 190 SpA patients from the rheumatology clinic were selected for the study. Guided phone questionnaires were administered by research staff to collect baseline characteristics, SpA disease status, and COVID-19 clinical outcomes. Cohabitants served as the control group and provided COVID-19 related data. Of the 190 potential SpA patients, 122 (66%) completed the questionnaire via phone, along with 259 cohabitants. 84.4% of SpA patients were diagnosed with Ankylosing Spondylitis (AS), and 15.6% were diagnosed with Psoriatic Arthritis (PsA). The rate of SARS-CoV-2 infection was 83.6% in the Secukinumab group and 88.8% in the cohabitants control group, with no significant difference (OR = 0.684, CI 0.366-1.275). One instance of severe COVID-19 was observed in the Secukinumab group, while two were identified in the cohabitants control group. Patients in the Secukinumab group had less time with fever caused by COVID-19 (p = 0.004). Discontinuing Secukinumab after SARS-CoV-2 infection did not significantly affect the course of COVID-19 or worsen SpA status according to our data. Our study suggests that administering Secukinumab to SpA patients does not increase their susceptibility to contracting SARS-CoV-2, and may have a positive effect on the course of SARS-CoV-2 infection.